Biodegradation of hydrocarbon by indegenous fungi isolated from oil-contaminated samples. - Jaya Seelan, Sathiya Seelan (Universiti Malaysia Sarawak (UNIMAS), 2004)
Morphological and physiological characteristics of Aspergillus spp. were studied. Eight isolates of Aspergillus spp. that has been isolated from plants and soils in Sarawak were used in this study. The identitication was done based on their morphological characteristics. The etlects of various semi-synthetic agar media, light, temperature, pH, different carbon sources and macro elements on growth rates of the Aspergillus spp. were examined. Optimum growth rates and sporulation of the fungi were atTected ditlerentially by these factors. There was significant ditTerence at P<0.05 of growth rates of the fungi on the ditTerent media. The faster growth rate occurred on potato dextrose agar (PDA) for all isolate of Aspergillus species except for A. carbonarius (742). This isolate had faster growth rate on yeast extract agar at 25-30°C. Different isolates of the Aspergillus showed ditlerent optimum temperature for growth. The optimum temperature range for grow1h ofA. nivells (518) was at 30-35°C; A. glaucus (542) was at 25-35°C and for A. lerreus (910) at 25-30°C. However, optimum temperature for growth of A. niger (1022), A . ./lavlJs (1044), A. alulaceus (1046) and A. oryzae (1047) was at 30°C and the growth rates were reduced as the temperatures were decrease or increase. There was significant effect of light on the growth rates of all the Aspergillus spp. All species except A. niger (1022) grew faster in dark. Growth test at different pH condition showed that all of the Aspergillus isolates grew more active at pH 5.0 except A. glaucus (542), it grew best at pH 6.0. All isolates of Aspergillus spp. were able to grow on media contain glucose, sucrose, soluble starch and lactose. The present study shows that the lactose was not suitable for sporulation. There was significant effect (P<0.05) on the growth rates of Aspergillus spp. on macro elements.